2012
DOI: 10.1002/rcm.6278
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the mass fragmentation pathways of the polyether marine toxins, dinophysistoxins, and identification of isomer discrimination processes

Abstract: RATIONALE Most of the liquid chromatography/mass spectrometry (LC/MS) methods that have been developed for the analysis of Diarrhetic Shellfish Poisoning (DSP) toxins in shellfish and algae samples have been unable to differentiate the isomers okadaic acid (OA) and dinophysistoxin‐2 (DTX2), unless separated by chromatography. Since there are many bioconversion products of these compounds it is imperative to determine characteristic product ions, which can provide unequivocal identification of OA and DTX2 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition to the retro-ene reaction, other typical charge-retention fragmentations, such as RDA at the B-ring, were also reported for these compounds. 86 In natural products with a prenyl side chain, such as avonoids, coumarins, and quinonoids, the elimination of the prenyl moiety involves a retro-ene reaction. Li and co-workers 87 reported that retro-ene reactions involved in the elimination of the oxygenated prenyl chain from protonated prenylated furanocoumarins (19) occurs through the participation of the double bond of the aromatic ring and results in the fragment ion of m/z 203 (Fig.…”
Section: Retro-ene Reactionsmentioning
confidence: 99%
“…In addition to the retro-ene reaction, other typical charge-retention fragmentations, such as RDA at the B-ring, were also reported for these compounds. 86 In natural products with a prenyl side chain, such as avonoids, coumarins, and quinonoids, the elimination of the prenyl moiety involves a retro-ene reaction. Li and co-workers 87 reported that retro-ene reactions involved in the elimination of the oxygenated prenyl chain from protonated prenylated furanocoumarins (19) occurs through the participation of the double bond of the aromatic ring and results in the fragment ion of m/z 203 (Fig.…”
Section: Retro-ene Reactionsmentioning
confidence: 99%
“…Table 3. [14,40,46,113,131,136,137]. * The TEF of the hydrolysis product of OA, DTX1 or DTX2 would apply [104].…”
Section: Chemical Method: Liquid Chromatography Coupled With Tandem Mmentioning
confidence: 99%
“…Based on their mass and specific fragmentation pattern, 85 different toxins were identified comprising 33 OA, 26 YTX, 18 AZA and 8 PTX group toxins. Comparison of the high-resolution product ion spectra of the polyether marine toxins, dinophysistoxins (DTXs), led to the identification of distinctive product ions which allowed these compounds for the first time to be identified and distinguished without the need for separation (Carey et al, 2012).…”
Section: Monitoring Natural Toxins Including Mycotoxins In Food and Feedmentioning
confidence: 99%